2023
DOI: 10.1590/s1519-994020220032
|View full text |Cite
|
Sign up to set email alerts
|

Oregano extract (Origanum vulgare) in female broiler chickens of free-range strain raised in the Western Amazon

Iuryane de Oliveira Sandra,
Fabio Augusto Gomes,
Henrique Jorge de Freitas
et al.

Abstract: This study aimed to evaluate the effect of oregano extract added to commercial diets on zootechnical performance parameters, carcass yield, immunological conditions, morphometry, and intestinal pH for free-range broiler chickens raised under sanitary challenge conditions. Three hundred chicks of the strain ‘Heavy red’ were used and distributed in a completely randomized experimental design with five treatments and six replications, totaling 30 experimental units, each consisting of 10 birds. The treatments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…FIG. 5 shows that there is no significant statistical difference between treatments with respect to viscera, these results in the liver percentage are similar to those found by Languido et al [17], in Bounty Fresh chickens, who in their experiment "Performance of Bounty Fresh Broiler Chicken Fed Diet Supplemented with Oregano (Plectranthus amboinicus L.) Leaf Meal", where they included P. amboinicus leaf meal in the diet in different percentages did not show any effect, although they differed from the findings of Sandra et al [16], who found lower percentages in the treatments with 350 and 450 mg•kg -1 of Oregano extract, these same authors did not report statistical differences in the data of heart, gizzard and intestinos. For the spleen and gizzard fat variables, no information was found to contrast the results.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…FIG. 5 shows that there is no significant statistical difference between treatments with respect to viscera, these results in the liver percentage are similar to those found by Languido et al [17], in Bounty Fresh chickens, who in their experiment "Performance of Bounty Fresh Broiler Chicken Fed Diet Supplemented with Oregano (Plectranthus amboinicus L.) Leaf Meal", where they included P. amboinicus leaf meal in the diet in different percentages did not show any effect, although they differed from the findings of Sandra et al [16], who found lower percentages in the treatments with 350 and 450 mg•kg -1 of Oregano extract, these same authors did not report statistical differences in the data of heart, gizzard and intestinos. For the spleen and gizzard fat variables, no information was found to contrast the results.…”
Section: Resultssupporting
confidence: 87%
“…Similarly, when the carcass yield was analyzed by Campozano-Marcillo et al [14], in their study " Aceite esencial de orégano (Origanum vulgare L.) y sexo como factores en la respuesta productiva en pollos de engorde", used 400 Cobb 500 broilers where they tested different concentrations of oregano essential oil, slaughtering 40 birds of 42 d of age, did not find + differences, it should be noted that they used a treatment with APC; this also differs from the findings of Batista et al [15], in their study "Antibioterapia natural para el tratamiento de la coccidiosis y su repercusión en el comportamiento productivo del broiler", using 120 broilers and evaluating for 45 d, and found differences when using the mother tincture (mixture tincture) at 20%, assuming that the garlic + Oregano combination was effective in this percentage mentioned above, emphasizing that there was a treatment with commercial coccidiostat. Regarding abdominal fat, Sandra et al [16], in their research "Oregano extract (Origanum vulgare) in female broiler chickens of free-range strain raised in the Western Amazon", using 300 female Heavy red broilers, where they tested different amounts of oregano extract, sacrificing 30 birds of 70 d of age, found differences, with a tendency to present a higher percentage of abdominal fat (5.81%) at a dose of 450 mg•kg -1 .…”
Section: Resultsmentioning
confidence: 99%